Literasi Keuangan, Perilaku Keuangan, Overconfidence dan Keputusan Investasi - Rahayu Pradnyani, Luh Gede Rai; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 33 No 5 (2023), 2023)
The number of investors in investing activities continues to increase every year, investment decision making involves knowledge, behavior, and investors' emotions. The aim of the study was to determine the effect of financial literacy, financial behavior and overconfidence on investment decisions and to find out the differences in financial literacy, financial behavior and overconfidence in making investment decisions with an investment duration of less than two years and more than two years. The population in this study were members of the Capital Market Study Group (KSPM) at Udayana University. The total sample is 138 respondents using a saturated sampling technique using a questionnaire as a method of data collection. The data analysis technique used is multiple linear regression and the Mann-Whitney test. The results of the study show that financial literacy, financial behavior and overconfidence have an effect on investment decisions. There are differences in financial literacy and overconfidence, but there are no differences in financial behavior in making investment decisions based on the length of investment. Keywords: Investment Decisions; Financial Literacy; Financial Behavior; Overconfidence